Time-resolved photoelectron angular distributions from nonadiabatically aligned CO2 molecules with SX-FEL at SACLA. (14th November 2018) - Minemoto, Shinichirou; Shimada, Hiroyuki; Komatsu, Kazma; Komatsubara, Wataru; Majima, Takuya; Miyake, Soichiro; Mizuno, Tomoya; Owada, Shigeki; Sakai, Hirofumi; Togashi, Tadashi; Yabashi, Makina; Decleva, Piero; et al.
Abstract: We performed time-resolved photoelectron spectroscopy of valence orbitals of aligned CO2 molecules using the femtosecond soft x-ray free-electron laser and the synchronized near-infrared laser. By properly ordering the individual single-shot ion images, we successfully obtained the photoelectron angular distributions (PADs) of the CO2 molecules aligned in the laboratory frame (LF). The simulations using the dipole matrix elements due to the time dependent density functional theory calculations well reproduce the experimental PADs by considering the axis distributions of the molecules. The simulations further suggest that, when the degrees of alignment can be increased up to ⟨ cos 2 θ ⟩ > 0.8, the molecular geometries during photochemical reactions can be extracted from the measured LFPADs once the accurate matrix elements are given by the calculations.